111. Impact of Microbiology Laboratory Result Presentation on Antibiotic Stewardship: Process Use Evaluation. (31st December 2020) - Brummett, Christina M; Harding, Stephanie; Beadle, Kathy; Jones, Shelley
Abstract: Background: Advancements in laboratory diagnostics are constantly occurring and accuracy in interpreting results directly affects optimal patient care. The purpose of this process use evaluation was to assess the efficacy of our current presentation of microbiology results in facilitating appropriate clinical decisions and antibiotic stewardship. Methods: A six question multiple choice survey was sent to prescribers and pharmacists. Each question used our healthcare system's current presentation of microbiology results. The recipients were asked to make a clinical decision based on patient history and results presented. The topics surveyed included de-escalation of antibiotics based on polymerase chain reaction (PCR) for positive blood cultures (Image 1), evaluation of C. difficile PCR and enzyme immunoassays (Image 2), impact of recent immunization on results of S. pneumoniae urine antigen (Image 3), susceptibilities of Group C Streptococcus and H. influenzae (Images 4 and 5), and understanding of minimum inhibitory concentrations (MIC, Image 6). The anonymous surveys were collected either electronically or by paper. Image 1 Image 2 Results: Several trends were seen in the 64 responses received (n, %). Questions with lab results containing detailed comments with guidance on how to interpret the results had the highest percentage of correct responses. This included our C. difficile (59, 92%) and S. pneumoniae urine antigen (61, 95%) results. Culture results with presumed susceptibilities and/or lack of guidance ( H. influenzae (55, 86%); Group C Streptococcus (46, 72%)) had lower rates of correct interpretation and resulted in provider reluctance to de-escalate antibiotics. A similar trend was seen with the word "presumptive" on blood culture results by PCR (37, 58%). MICs were frequently misinterpreted as being able to compare activity between antibiotics (46, 72%). Image 3 Image 4 Image 5 Conclusion: This study highlights that stewardship programs should focus on how lab results are reported and interpreted and should work with their microbiology lab to determine the presentation of results. Additions of detailed interpretations to Microbiology results may lead to improved de-escalation and antibiotic selection. Image 6 Disclosures: All Authors : No reported disclosures